Investment Fund’s Liquidity Risk Management in the Event of a Net Outflow - Davtyan, Tigran (Bulletin of Yerevan University G: Economics, 2022)
As a rule, open-end investment funds are obliged to return the invested funds at the request of the investors, i.e. to redeem the units of the funds. As the fund's assets are invested in financial assets that are less liquid than cash, liquidity risk arises, the management of which should be given special attention by the fund manager, especially in the event of a large outflow from the fund.A model is introduced in this article, the solution of which leads to the optimal volume of the fund’s cash and financial assets for sale, which enables to manage the liquidity risk at the lowest cost. In other words, it becomes possible to form the investment portfolio of the fund with such assets, the proceeds from the sale of which will be sufficient to cover the net outflows of investments from the fund, and the sum of the costs of selling assets and the alternative cost of investing cash will be minimized. In addition, the Value at Risk (VaR) method is used to assess the risk of net outflow of investments from the fund, which is based on historical data of outflows from the fund. Then, the net outflow risk is estimated for the one of the Armenian investment funds, and the effectiveness of the model for the liquidity risk management is illustrated.
Keywords: net outflow; liquidity risk; nonlinear programming; bid-ask spread; opportunity cost; open-end investment fund; redemption of shares